Study on the mechanism of Codonopsis pilosula polysaccharide inhibiting gastric cancer precancerous lesions by regulating Wnt/β-catenin signaling pathway - Zi-xia Wang; Peng-peng Li; Cheng-nan Li; Yi-na Guo; Ya-zhou Shao; Qiao Yan; Long-xia Wen; Yan-ping Wang; Fang-Di Hu (Elsevier, 2024)
Aim: To investigate the effect of Codonopsis pilosula polysaccharide (CPP) on precancerous lesions of gastric cancer (PLGC) and its mechanism. Methods: The CPP with more than 90 % sugar content was prepared by water extraction and alcohol precipitation combined with column chromatography. MTT assay was used to analyze the effect of CPP on the survival rate of human normal gastric epithelial cells (GES-1) and the proliferation of human gastric adenocarcinoma cells (AGS). The PLGC animal model was induced by chemical combined with irregular diet. The alleviate effect and related mechanism of CPP at high and low doses (110 mg/kg and 440 mg/kg) on PLGC were further analyzed. Results: CPP can significantly promote the proliferation of hypoxia-induced GES-1 cells and after 48 h of CPP treatment, the expressions of Wnt-1, β-catenin and TCF-4 in GES-1 cells were significantly increased (P < 0.05). CPP can significantly inhibited the growth of AGS cells and after 48 h of CPP treatment, the expression of Wnt-1, β-catenin and TCF-4 in AGS cells was significantly decreased (P < 0.05). In the PLGC animal model, CPP could alleviate the damage degree of PLGC, inhibit the weight loss of rats, and significantly improve the levels of serum markers. Further, Western blot results showed that in the gastric tissue of rats, CPP could significantly increase the expression of Wnt-1β-catenin and TCF-4, and significantly decreased the ratio of Bcl-2/Bax, and significantly increased the expression level of caspase-3. The results of serum metabolomics analysis of rats showed that CPP may improve PLGC by affecting glycine metabolism, serine metabolism, threonine metabolism and other pathways. Conclusions: This study confirms that CPP can alleviate PLGC. At the cellular level, CPP can play a protective role in gastric mucosa by activating Wnt/β-catenin signaling pathway under inflammatory or oxidative stress conditions, and can promote the apoptosis of abnormal cells of gastric glands by inhibiting Wnt/β-catenin signaling pathway. At the animal level, CPP can not only inhibit PLGC by inhibiting Wnt/β-catenin signaling pathway, but also alleviate PLGC by promoting abnormal apoptosis in gastric tissue.